Severe obstetric morbidity - near miss. Meaning for surviving women: oral history. - Maria Alice Tsunechiro; Dulce Maria Rosa Gualda; Roselena Bazilli Bergamasco; Sandra Regina de Godoy (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2008)
The aim of this study was to understand the meaning of the near miss experience during pregnancy, labor, birth and puerperium in the life of the women who survived. The conceptions of Medical Anthropology were used as the theoretical framework for the analysis and the Oral History as the methodological reference. The research was developed including women who live in a micro-region of the northwest of São Paulo state and Fernandópolis district. Thirteen women who returned from the intensive care unit of a municipal general hospital, from 2003 to 2005, participated in this study. The interviews were presented as narratives. The data showed that the experience of a severe complication with risk of death was remarkable, unpleasant, evidencing feelings of suffer, fear and worry. The women noticed that "something is wrong", then they looked for a health service unit and evaluated the assistance given. The main women's worry was related to the child, the husband and the family. The findings of this study permitted to have a comprehensive vision of the experience of the women who faced the risk of maternal death and survived, as well as the changes in their lives and the ways of coping and overcoming the difficulties found.